2021
DOI: 10.3390/ani11113200
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Profile of Blood Plasma at Mating and Early Gestation in Rabbit

Abstract: The aim of this study was to analyse the fatty acid (FA) profile of blood plasma at mating and 72 hpm by gas chromatography. Moreover, the correlation between FA and ovulation rate, normal embryos and compacted morulae was estimated. Palmitic, linoleic, oleic and stearic were the highest FA concentrations at mating and 72 hpm. Most long chain saturated and PUFA were higher at 72 hpm than at mating, while MUFA were higher at mating. SFA, MUFA and PUFA were high and positively correlated. Correlation was 0.643 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…In our study, soya lecithin induced periovarian adipocyte hypertrophy, increased the level of unsaturated fatty acids particularly the MUFA suggesting a possible positive role of lysolecithin on reproductive performance of rabbit does. This is also supported by the observations of other researchers that the increased MUFA in the blood of female rabbits before mating increased the ovulation rate and number of offspring (Hadjadj et al, 2021;Mattioli et al, 2019). Soya lecithin increased blood glucose levels when fed to rabbits (Attia et al, 2018), helping to explain the observed adipocyte hypertrophy in periovarian fat in our study.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, soya lecithin induced periovarian adipocyte hypertrophy, increased the level of unsaturated fatty acids particularly the MUFA suggesting a possible positive role of lysolecithin on reproductive performance of rabbit does. This is also supported by the observations of other researchers that the increased MUFA in the blood of female rabbits before mating increased the ovulation rate and number of offspring (Hadjadj et al, 2021;Mattioli et al, 2019). Soya lecithin increased blood glucose levels when fed to rabbits (Attia et al, 2018), helping to explain the observed adipocyte hypertrophy in periovarian fat in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Marounek et al [ 42 ] reported that with increasing levels of dietary supplementation of unsaturated acid (CLA) to rabbits, the concentration of CLA in tissue lipids increased. Hadjadj et al [ 43 ] noted correlations between blood fatty acid levels and ovulation rate and embryonic development. Mattioli et al [ 10 ] reported that enrichment of the diet with n-3 fatty acids can be considered a good strategy to improve reproductive performance in rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, fatty acids (FAs) have a variety of essential biological roles and are considered one of the functional nutrients and chemicals. Triglycerides, for example, are employed as precursors for the production of vital energyproducing metabolites [13] and oocytes and embryos use it as an energy substrate for differentiation, development, and immune system activity [14]. FAs serve as useful chemicals for a variety of reproductive processes.…”
Section: Nutritional Description Of Moringa Oleiferamentioning
confidence: 99%